ANALISIS BUTIR SOAL KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DENGAN MENGGUNAKAN GRADED RESPONSE MODEL (GRM) - Ariyanti, Davi; Ihsanudin, Ihsanudin; Khaerunnisa, Etika (Universitas Sultan Ageng Tirtayasa, 2019)
This research aims to analyze the items about mathematical problem solving ability using Graded Response Model (GRM). and obtain overview about mathematical problem solving ability. The main instrument in this study was the researcher ownself assisted with observation sheets, tests of mathematical problem solving abilities, and interview guidelines. The research subjects were student first grade of SMP Negeri 3 Cilegon with 28 people selected by one person in each category, namely very high, high, medium, low and very low. There are 4 steps to solving mathematical problem solving abilities used in this study, namely understanding the problem, devising a plan, carrying out the plan, and looking back. The results showed that 1) students who had very high mathematical problem solving abilities were able to do all stages, 2) students with high mathematical problem solving abilities were able to understand the problem, devising plan, and carrying out the plan, 3) students who have medium mathematical problem solving abilities were able to solve problems in the steps of understanding the problem and devising plan, 4) students with low problem solving abilities are only able to understand the problem, 5) students with very low mathematical problem solving abilities are unable to do anything.